Analysis of vegetation dynamics in the Qinling-Daba Mountains region from MODIS time series data - Yan Bai (Elsevier, 2021)
The Qinling-Daba Mountains region (Qinba) is an important geographical transitional zone across the north and south of China. To comprehensively understand the ecological transition in the Qinba over past two decades, this study assessed and predicted the spatiotemporal variations of vegetation comparatively, using 250-m time series MODIS NDVI and EVI products. From 2000 to 2019, remarkable increases were observed both in annual and seasonal NDVI and EVI (P < 0.05), and the increasing rate of NDVI was higher than that of EVI for all temporal scales, except summer. Compared to NDVI, larger areas of no significant change were obtained in annual, autumn, and winter EVI, primarily distributed in the high-altitude regions of western Qinba. All assessed vegetation types increased significantly during past two decades except alpine vegetation and marsh, however, the seasons in which the significant increase in NDVI and EVI occurred varied for different vegetation types. Hurst exponent analysis suggested that inconsistent characteristics of vegetation dynamic trends were stronger in the future across Qinba. The area proportion of unfavorable trends, identified mainly covered with cultivated vegetation and scrub, was much larger than that of favorable trends, especially detected by EVI. Areas likely to experience vegetation variation of unfavorable and undetermined trends deserve high focus.